1984
DOI: 10.1148/radiology.152.3.6463260
|View full text |Cite
|
Sign up to set email alerts
|

Ear, nose, and throat cancer: ultrasound diagnosis of metastasis to cervical lymph nodes.

Abstract: We present the results of a study on the value of ultrasound in the detection of metastasis to the cervical lymph nodes in connection with cancer of the ear, nose, and throat. Comparison of clinical, ultrasound, and histological findings for 100 patients who underwent surgery revealed that clinical examination had a sensitivity of 78% versus 92.6% for ultrasound. All 18 cases of thrombosis of the internal jugular vein were detected by ultrasound. Clinical staging of the disease was modified in 28 of these pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0
7

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(61 citation statements)
references
References 0 publications
2
52
0
7
Order By: Relevance
“…Ultrasonic features of malignant lymphomas particularly in infiltration of cervical lymph nodes have been described as involvement of multiple nodes [3,10], round shape [11], homogeneous or a slightly echogenic internal echo [1,3], tubular structure [9], and posterior enhancement [10,11]. In this study, we confirmed some of these features, such as involvement of multiple nodes and posterior enhancement as common among various histopathological subtypes.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Ultrasonic features of malignant lymphomas particularly in infiltration of cervical lymph nodes have been described as involvement of multiple nodes [3,10], round shape [11], homogeneous or a slightly echogenic internal echo [1,3], tubular structure [9], and posterior enhancement [10,11]. In this study, we confirmed some of these features, such as involvement of multiple nodes and posterior enhancement as common among various histopathological subtypes.…”
Section: Discussionsupporting
confidence: 84%
“…It has been useful in differentiating malignant lymphoma from other diseases such as metastatic mass [1][2][3], in determining the stage of the lymphoma, and in monitoring responsiveness to treatment [4]. Because malignant lymphomas comprise a variety of histopathological subtypes with different responsiveness to treatment and prognosis, a final diagnosis and subtyping is ordinarily done by a histopathological examination of biopsy specimens.…”
Section: Introductionmentioning
confidence: 99%
“…A sensitivity of 92.6% for the same was seen in a study comparing clinical, US, and histological findings for 100 patients. 23 Thus, US has a high sensitivity and specificity in diagnosing all types of neck swellings -congenital, inflammatory, benign and malignant. It correctly diagnosed 89 out of 100 neck swellings in this study.…”
Section: Discussionmentioning
confidence: 99%
“…6,9,16,17 High resolution ultrasound (US) is reported to be more sensitive than clinical examination (92 per cent versus 70 per cent) in detecting and differentiating benign from malignant nodes. 18 Furthermore, the specificity of US combined with guided FNAC has been reported to be as high as 92.7 per cent. 19 However, Ahuja and colleagues' study of patients with nasopharyngeal carcinoma found that, for up to three months after radiotherapy, apart from a decrease in node size and the appearance of oedema, other features of previously abnormal nodes (i.e.…”
Section: Discussionmentioning
confidence: 99%